Qualitative differences in the spatiotemporal brain states supporting configural face processing emerge in adolescence in autism. (October 2022) - Haartsen, Rianne; Mason, Luke; Garces, Pilar; Gui, Anna; Charman, Tony; Tillmann, Julian; Johnson, Mark H.; Buitelaar, Jan K.; Loth, Eva; Murphy, Declan; Jones, Emily J.H.; ,; et al.
Abstract: Background: Studying the neural processing of faces can illuminate the mechanisms of compromised social expertise in autism. To resolve a longstanding debate, we examined whether differences in configural face processing in autism are underpinned by quantitative differences in the activation of typical face processing pathways, or the recruitment of non-typical neural systems. Methods: We investigated spatial and temporal characteristics of event-related EEG responses to upright and inverted faces in a large sample of children, adolescents, and adults with and without autism. We examined topographic analyses of variance and global field power to identify group differences in the spatial and temporal response to face inversion. We then examined how quasi-stable spatiotemporal profiles – microstates – are modulated by face orientation and diagnostic group. Results: Upright and inverted faces produced distinct profiles of topography and strength in the topographical analyses. These topographical profiles differed between diagnostic groups in adolescents, but not in children or adults. In the microstate analysis, the autistic group showed differences in the activation strength of normative microstates during early-stage processing at all ages, suggesting consistent quantitative differences in the operation of typical processing pathways; qualitative differences in microstate topographies during late-stage processing became prominent in adults, suggesting the increasing involvement of non-typical neural systems with processing time and over development. Conclusions: These findings suggest that early difficulties with configural face processing may trigger later compensatory processes in autism that emerge in later development.